A geopolitical analysis of First Nations’ territorial strategies towards self-determination in Canada : Urban Reserves in Saskatoon and Winnipeg - Bezamat-Mantes, Charlotte (HAL CCSD, 2020)
In Canada, First Nations peoples – one of the three Indigenous peoples – often live in difficult socio-economic conditions and their governments heavily depend on federal funding, which restricts the exercise of their right to self-determination. Some First Nations are implementing an unprecedented urban economic development strategy through the establishment of urban Indian reserves – a process laden with power rivalries between Indigenous, federal, municipal and provincial governments, vying for control over land. This dissertation offers a geopolitical analysis of the way urban reserves re-shape First Nations’ intergovernmental relations by redefining their roles and place in the city. Three cases of urban reserves are analysed: the Long Plain First Nation’s and the Treaty One First Nations’ in Winnipeg, and the Muskeg Lake Cree Nation’s in Saskatoon. They show that urban reserves are intergovernmental contact zones shaped by power rivalries which favour federal and municipal governments. First Nations’ presence in the city is accepted when it is economic in nature, but their political authority is disputed by municipalities and constrained by the federal Indian Act. Urban reserves help increase Indigenous governments’ economic self-sufficiency, and thus their political autonomy, but they also result in a strict federal and municipal regulation of Indigenous sovereignty in urban territories. Au Canada, les membres des Premières Nations – l’un des trois peuples autochtones – connaissent souvent des conditions socio-économiques difficiles et leurs gouvernements sont financièrement dépendants du gouvernement fédéral, ce qui restreint la mise en œuvre de leur droit à l’autodétermination. Certaines Premières Nations mettent en place une stratégie de développement économique urbain inédite, grâce à l’établissement de réserves indiennes en ville, qui catalysent des rivalités de pouvoir pour le contrôle du territoire entre les gouvernements autochtones, fédéral, municipaux et provinciaux. Cette thèse utilise la ...